Randomized double blind trial of prednisolone and azathioprine, vs. prednisolone and placebo, in the treatment of pemphigus vulgaris. (15th October 2012) - Chams‐Davatchi, C.; Mortazavizadeh, A.; Daneshpazhooh, M.; Davatchi, F.; Balighi, K.; Esmaili, N.; Akhyani, M.; Hallaji, Z.; seirafi, H.; Mortazavi, H.
Abstract Background The classic treatment for pemphigus vulgaris is prednisolone. Immunosuppressive drugs can be used in association. Objective To compare the efficacy of Azathioprine in reducing the Disease Activity Index (DAI). Patients and methods A double blind randomized controlled study was conducted on 56 new patients, assigned to two therapeutic groups: (i) prednisolone plus placebo; (ii) prednisolone plus Azathioprine. Patients were checked regularly for 1 year. 'Complete remission' was defined as healing of all lesions after 12 months, and prednisolone <7.5 mg daily, (DAI ≤ 1). Analysis was done by 'Intention To Treat' (ITT) and 'Treatment Completed Analysis' (TCA). Results Both groups were similar in age, gender, disease duration, and DAI. Primary endpoint: By ITT and TCA, the mean DAI improved in both groups with no significant difference between them. The difference became significant for the last trimester (3 months; ITT: P = 0.033, TCA: P = 0.045). Secondary endpoint: The total steroid dose decreased significantly in both groups, with no significant difference between them, except for the last trimester (ITT: P = 0.011, TCA: P = 0.035). The mean daily steroid dose decreased gradually in both groups becoming statistically significant in favour of azathioprine, in the last trimester, especially at 12th months (ITT: P = 0.002, TCA: P = 0.005). Complete remission was significant at 12 months only for TCA (AZA/Control: 53.6%/39.9%, P = 0.043). Limitations Sample size was rather small to demonstrate all differences. Other limitations include the choice of primary and secondary endpoints and the unavailability to measure thiopurine methyltransferase activity. Conclusion Azathioprine helps to reduce prednisolone dose in long‐run.